VIV study of an elastically mounted cylinder having low mass-damping ratio using RANS model - Khan, Niaz Bahadur; Ibrahim, Zainah; Khan, Muhammad Ijaz; Hayat, Tasawar; Javed, Muhammad Faisal (Elsevier, 2018)
This study addresses vortex-induced vibration analysis by an elastic rigid cylinder oscillating free in cross flow direction subject to low mass damping ratio. Two-dimensional Reynold-Averaged Navier-Stokes equations (RAN) for this purpose are simulated. Analysis is carried out for range of reduced velocity = 2–16 which corresponds to Reynolds number 1700–14,000. The mass-ratio is 2.4 and mass-damping ratio 0.0013. Previously, similar studies have been performed numerically but are limited to achieve maximum cylinder response. In the current study, comparatively higher value of maximum amplitude of cylinder is computed. However delay in transition from ‘upper branch’ to ‘lower branch’ is noticed. In addition to maximum amplitude, other hydrodynamic coefficients are also discussed. The results extracted from current simulations are compared with previous experimental studies in literature.